An Analysis of Linguistic Competence of Phonology Teaching on YouTube Video Series - Neng Herawani; Ratna Dewanti (Indonesian Journal of Foreign Language Studies, 2026)
Linguistic competence plays a pivotal role for English teachers in assisting the students for developing their language acquisition. Thus, a teacher's ability to accurately and thoroughly explain language norms and structures which is primarily attributed to their linguistic competency is necessary. The purpose of this study is to examine linguistic competence in phonology teaching, which was demonstrated by an English teacher. This study used a descriptive qualitative method. The data was obtained from a series of videos of the phonology teaching which were broadcasted by an English teacher on a YouTube channel. The finding indicated that the teacher has adequate phonological knowledge either in case of material mastery and producing English sounds in giving some examples while delivering the linguistic materials particularly in phonology. Furthermore, linguistics is valued as an important component in teaching a language. It can raise a teacher's knowledge of language, which would make them more capable and, ultimately, better language teachers.